Phylogenetic diversity patterns reveal contrasting and spatially dependent evolutionary histories in a hyper-diverse montane vegetation complex - Souza, Yago Barros de (2021)
Old, climatically buffered, infertile landscapes (OCBILs) comprise some of the world\'s most diverse floras. Such floras, according to OCBIL theory, are expected to favour the persistence of old lineages. Nevertheless, recent and fast diversification apparently played a major role in the evolutionary history of a Neotropical OCBIL, the campos rupestres. Here we aimed to elucidate the distribution of concurrent evolutionary processes by assessing fine spatial patterns of phylogenetic diversity and endemism in the campos rupestres. Based on predictions of the OCBIL theory and on the insular nature of this vegetation, we proposed that (1) patterns of phylogenetic overdispersion and paleo-endemism predominate, revealing a flora mainly composed by relatively old lineages. Furthermore, (2) both the taxonomic and the phylogenetic composition should be highly geographically structured if present and past barriers to dispersion have restricted spatial connections between different parts of the campos rupestres. To test those hypotheses, we calculated taxonomic and phylogenetic alpha and beta diversity metrics and conducted categorical analyses of neo- and paleo-endemism (CANAPE) for six campos rupestres\' representative angiosperm groups. Our analyses were based on occurrence data gathered from herbaria databases and on recently published, well-sampled phylogenetic hypotheses. We defined grid cell\'s size according to redundancy values in order to maintain satisfactory sampling rates while preserving spatial resolution. We found that phylogenetic overdispersion predominates in the campos rupestres flora. However, this general pattern is permeated by both lineage- and site-specific phylogenetic clustering, suggesting that recent diversification events depend on particular regional conditions and on the overall maintenance of old lineages across the campos rupestres. CANAPE shows that endemism patterns differ between regions, but paleo-endemism is widespread and particular prominent where phylogenetic overdispersion is more evident. Moreover, although taxonomic composition is highly geographically structured and seems to be influenced by different types of surrounding vegetation, phylogenetic composition indicates past spatial connections that might have been established by different processes. These results highlight the importance of considering the spatial component when investigating diversification patterns and suggest that the flora of old, climatically buffered, infertile landscapes might have been shaped by spatially dependent evolutionary processes.